2020
DOI: 10.1093/jalm/jfaa125
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-Head Comparison of Two SARS-CoV-2 Serology Assays

Abstract: Background While molecular techniques remain the gold standard for diagnosis of acute SARS-CoV-2 infection, serological tests have the unique potential to ascertain how much of the population has been exposed to the COVID-19 pathogen. There have been limited published studies to date documenting the performance of SARS-CoV-2 antibody assays. Methods We compared the DiaSorin Liaison SARS-CoV-2 S1/S2 IgG and Roche Diagnostics E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 11 publications
4
28
0
Order By: Relevance
“…This variability in assay performance should be considered when selecting an EIA to detect antibodies against SARS-CoV-2 and/or high nAbs among recovered persons.Consistent with our findings, there is growing evidence that both the Abbott and Roche assays have comparable performance characteristics that are often superior to many other commercially available ELISAs to detect IgG or total antibodies against SARS-CoV-2 in convalescent individuals 19,20. Although we did not include "challenge" specimens to examine potential crossreactivity of antibodies to other pathogens, others have shown limited evidence of crossreactivity for the Euroimmun, EDI, Roche, and Abbott assays 19,[21][22][23][24][25]. Data on the performance of the ImmunoDiagnostics ELISA to detect SARS-CoV-2 antibodies are limited.Large public health laboratories and large blood collection centers often rely on automated serological platforms-like those by Roche and Abbott-for screening of multiple pathogens including SARS-CoV-2.…”
supporting
confidence: 82%
“…This variability in assay performance should be considered when selecting an EIA to detect antibodies against SARS-CoV-2 and/or high nAbs among recovered persons.Consistent with our findings, there is growing evidence that both the Abbott and Roche assays have comparable performance characteristics that are often superior to many other commercially available ELISAs to detect IgG or total antibodies against SARS-CoV-2 in convalescent individuals 19,20. Although we did not include "challenge" specimens to examine potential crossreactivity of antibodies to other pathogens, others have shown limited evidence of crossreactivity for the Euroimmun, EDI, Roche, and Abbott assays 19,[21][22][23][24][25]. Data on the performance of the ImmunoDiagnostics ELISA to detect SARS-CoV-2 antibodies are limited.Large public health laboratories and large blood collection centers often rely on automated serological platforms-like those by Roche and Abbott-for screening of multiple pathogens including SARS-CoV-2.…”
supporting
confidence: 82%
“…In the two-test approach, the overall result was considered positive if the sample tested positive by both assays and negative if the sample was negative using one or both assays. When calculating the positive predictive value (PPV) or negative predictive value (NPV) at various prevalence rates, assay sensitivity was defined as the observed sensitivity using samples collected >14 days after symptom onset (when sensitivity is reported to be its highest) ( 8 10 ). Specificity was defined (for PPV and NPV calculations) as the value obtained when all control samples were combined.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the relatively low prevalence of COVID-19 infection in many tested populations and the implications of false-positive results for patient care and public health measures, the Centers for Disease Control and Prevention (CDC) has determined that highly specific (≥99.5%) serologic tests are required to provide adequate positive predictive value (PPV) ( 7 ). Although high specificity is reported for many commercial SARS-CoV-2 serologic assays, not all of them consistently meet this specificity threshold (see Table S1 in the supplemental material) ( 8 10 ). A potential approach to ensure consistently high specificity involves the application of a two-test algorithm in which reactivity using one assay is confirmed using a different (orthogonal) assay.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that these assays become positive, at the earliest, 5 to 7 days after COVID-19 RT-PCR positivity and are nearly 100% positive by 3 weeks. 12,13 Deidentified existing plasma samples from 103 healthy individuals collected at least 1 year prior to the COVID-19 outbreak were tested as negative controls. Discrepancies between the DiaSorin and Roche assays were resolved using a third assay: the EUROIMMUN Anti-SARS-CoV-2 enzyme-linked immunosorbent assay (ELISA) IgG.…”
Section: Methodsmentioning
confidence: 99%